2021
DOI: 10.1002/cad.20404
|View full text |Cite
|
Sign up to set email alerts
|

“Se extraña todo:” Family separation and reunification experiences among unaccompanied adolescent migrants from Central America

Abstract: There has been a record surge of unaccompanied immigrant minors (UAMs) entering the United States, with 86% of those apprehended at the US-Mexico border originating from the Central American countries of El Salvador, Guatemala, and Honduras. A majority of immigrant children are separated from either one or both parents at various points during the migration process. Although average separations last 4 or more years, and may be deeply distressing, there is little research on family separations among Central Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
2
0
2
Order By: Relevance
“…There is a considerable body of literature [17,18,43] indicating that family separation is one of many adversities children and families experience before, during, and after migration, and it negatively impacts individuals' health and well-being [8,16,43] and the parent-child relationships [15,17]. The findings of the current study are consistent with other studies in this regard.…”
Section: Trauma Of Separationsupporting
confidence: 89%
See 1 more Smart Citation
“…There is a considerable body of literature [17,18,43] indicating that family separation is one of many adversities children and families experience before, during, and after migration, and it negatively impacts individuals' health and well-being [8,16,43] and the parent-child relationships [15,17]. The findings of the current study are consistent with other studies in this regard.…”
Section: Trauma Of Separationsupporting
confidence: 89%
“…A qualitative study of 30 UMC reunified with their parents demonstrated that reconnecting with parents after a long separation was a problem for the youth, leading to isolation, loneliness among children, and disruption of traditional family roles [17]. Another qualitative study with 42 UMC found that protracted separation was distressing and multifaceted, with many developmental implications for the youth [18]. These studies recommend providing developmentally appropriate and culturally responsive care to foster healthy adjustment among UMC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Immigrant youth leave their countries for a variety of reasons, including to reunite with family members, seek safer living conditions, and escape extreme poverty and violence (United Nations High Commissioner for Refugees, 2014 ). Before, during, and following migration, immigrants may be exposed to violence, family separation, political and economic uncertainty, barriers to basic needs and human rights, and a difficult context of reception (e.g., anti‐immigrant political climate; Birman, 2011 ; Patel et al, 2016 , 2021 ; Sangalang et al, 2019 ). This exposure to poverty, violence, political uncertainty, and instability places migrant youth among the most vulnerable to developing psychological distress, traumatic stress reactions, and decreased well‐being (Bean et al, 2007 ; Derulyn et al, 2009 ; Hodes, 2000 ; Michelson & Sclare, 2009 ; Thibeault et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 Padres o madres de NNA migrantes frecuentemente han migrado antes que sus hijos, lo que hace que la relación con ellos sea transnacional, 5 y en la que ahora la principal figura de apego es un tío, el abuelo o la hermana. 6 Esto implica que NNA busquen una reunificación con padres que no conocen con el objetivo subyacente de ayudar económicamente a alguien de su familia extensa o para escapar de amenazas de las maras. 6 La ausencia física familiar expone a los NNA a mayor riesgo ante los peligros del tránsito migratorio: trata de personas, discriminación y violencia física y sexual.…”
unclassified
“…6 Esto implica que NNA busquen una reunificación con padres que no conocen con el objetivo subyacente de ayudar económicamente a alguien de su familia extensa o para escapar de amenazas de las maras. 6 La ausencia física familiar expone a los NNA a mayor riesgo ante los peligros del tránsito migratorio: trata de personas, discriminación y violencia física y sexual. 7,8 Estas condiciones sociales tienen un impacto en la salud mental, por lo que se considera para este artículo un enfoque psicosocial donde se toman en cuenta tales condiciones -incluyendo razones para salir, relación con la familia e impacto del género-y las psicológicas, como sentimientos y vivencias que afectan el bienestar emocional.…”
unclassified